DARI DESA KITA BANGUN NEGERI LEWAT PENDIDIKAN KITA BERSINERGI - Eyra Aisyah Jasmine; Mahvira Aulia Lubis; Mutiara Fadilah Al Panzil; Syafani Salsabila (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Awareness of education in Indonesia is still very low, especially in remote areas. It is very unfortunate. In the midst of the era of globalization and modernization, the more sophisticated technology is still a lot of people who do not appreciate how the importance of education, especially in the education. Because highly educated people will not have narrow thoughts about the future, they are oriented toward their future. Highly educated people will also live with the norms prevailing in society. They know what to do with their future, will not give up or surrender to the circumstances. Conversely, people or parents who have a narrow mindset that considers education unimportant, causing their children who do not receive education will be a burden for the community. There are some objective issues that make people tend not to attach importance to religious education. The first is ignorance of the importance of education for survival. Many of them rural communities who think narrowly about formal education or non formal, whereas education plays an important role to support their lives in the future. For that I have some solutions that can be done to reduce the low awareness of education. By way of socialization about the importance of formal education and non formal for the life of civil society.